Smoking and Cerebrovascular Disease: A Three-phase Research Program - Edjoc, Rojiemiahd (Université d'Ottawa / University of Ottawa, 2013)
Purpose: The purpose of this research program was three-fold. First it aimed to determine the effectiveness of smoking cessation interventions in increasing cessation rates in smokers with cerebrovascular disease and whether smoking cessation reduces stroke recurrence. Second it aimed to determine the prognostic influence of smoking and its association with stroke severity, disability, length of stay in hospital and mortality. Third it aimed to identify multi-level correlates of smoking cessation in Canadians who reported stroke symptoms in a large population based survey. Methods: Two systematic reviews and meta-analyses were performed to achieve the first objective. For the second objective, a retrospective cohort study was undertaken using variables from the Registry of the Canadian Stroke Network. Finally, the third objective was achieved by analyzing respondents from the Canadian Community Health Survey. Results: There is a paucity of intervention studies examining the effectiveness of smoking cessation in smokers with cerebrovascular disease. Most intervention studies that were found, failed to employ evidence-based approaches to smoking cessation. No evidence was found in regards to the effect of smoking cessation on stroke recurrence. We found smokers had strokes at a younger age compared to non-smokers. We found that in transient ischemic attacks and intracerbral haemorrhage, smoking was a significant predictor of stroke severity, disability, length of stay in hospital and 1 year mortality. Correlates of smoking cessation among Canadians who have experienced symptoms of a stroke included: higher education and income, implementation of household and vehicle smoking restrictions, access to a general practitioner and the use of smoking cessation pharmacotherapies and counselling support. Co-morbidities such as depression and alcohol consumption reduced the likelihood of successful cessation. Conclusions: This three-phase research program elucidated the gaps in intervention research for this population along with co-morbidities that hinder success in cessation. Smoking negatively impacted outcomes such as disability, hospital length of stay and mortality in patients with transient ischemic attacks and intracerebral haemorrhage strokes. Future interventions should take into account modifiable smoking cessation correlates in order to increase cessation rates in smokers with cerebrovascular disease.
Keywords: Smoking; Stroke; Epidemiology; Multi-level Interventions